Hot carrier relaxation of Dirac fermions in bilayer epitaxial graphene. (2nd April 2015) - Huang, J; Alexander-Webber, J A; Janssen, T J B M; Tzalenchuk, A; Yager, T; Lara-Avila, S; Kubatkin, S; Myers-Ward, R L; Wheeler, V D; Gaskill, D K; Nicholas, R J
Abstract: Energy relaxation of hot Dirac fermions in bilayer epitaxial graphene is experimentally investigated by magnetotransport measurements on Shubnikov–de Haas oscillations and weak localization. The hot-electron energy loss rate is found to follow the predicted Bloch–Grüneisen power-law behaviour of T 4 at carrier temperatures from 1.4 K up to ∼100 K, due to electron-acoustic phonon interactions with a deformation potential coupling constant of 22 eV. A carrier density dependence in the scaling of the T 4 power law is observed in bilayer graphene, in contrast to the dependence in monolayer graphene, leading to a crossover in the energy loss rate as a function of carrier density between these two systems. The electron–phonon relaxation time in bilayer graphene is also shown to be strongly carrier density dependent, while it remains constant for a wide range of carrier densities in monolayer graphene. Our results and comparisons between the bilayer and monolayer exhibit a more comprehensive picture of hot carrier dynamics in graphene systems.